KAJIAN TEORITIS (5-TERSIER-BUTIL-2-METOKSIFENIL)-BENZOFENON SEBAGAI SENYAWA TABIR SURYA DENGAN METODE DFT-B3LYP - Fauziah Rofiq, NIM. 16630022 (2021)
Computational studies have been carried out to (5-tertiary-butyl-2-methoxyphenyl)-benzophenone (5TBMFB) as a sunscreen. The research uses the DFT (Density Functional Theory) and TD-DFT (Time Dependent-Density Functional Theory) basis set B3LYP/6-31G(d) using ORCA software. DFT is a method to calculate the total electronic energy and electron density distribution of compounds and TD-DFT is a method to investigate its optical and electrochemical properties. Calculations include the optimization energy in the 4-tersier-butylphenol (4TBF) methylation reaction with the methyl group of dimethyl carbonate were continued Friedel-Crafts acylation reaction with benzoyl chloride, bond length, HOMO-LUMO energy, and absorption in the UV region. The results obtained based on energy optimization (DFT) that 4TBF through methylation reaction to generate more stable structure, and the resulting bond length shows that it can bind to benzoyl chloride through the Friedel-Crafts acylation reaction. Meanwhile, TD-DFT produces a HOMO-LUMO energy difference of 4.26 eV and has an optimum absorption at 264-301 nm in the UV-B region.